THE FUTURE ATCO OFFICERS’ INDIVIDUAL PROFILES FORMING - Kolotusha, Volodymyr (Proceedings of National Aviation University (archive), 2021)
The aim: The aim of this article, taking into account aviation personnel professional training evolution and information technologies development, is a presentation of approach to problems solving, relating to future air traffic controllers training personalization by means of training individual profiles forming, taking into account their cognitive characteristics. The method: The approach, which is based on selected criteria – oriented test, by means of which the proper training styles defined, is described in this article. The results: depending on the defined training style, the variants of instructor’s guidance of knowledge, skills and habits acquisition process will be defined. The discussion: In future it provides the possibility to project the training packages according to ‘pupils’ individualized cognitive abilities, relating to reception of professionally oriented training materials.